A walk through Jubilees : studies in the Book of Jubilees and the world of its creation - Kugel, James L. (Supplements to the Journal for the Study of Judaism, 2012)
The first part of this book is an extensive verse-by-verse commentary on the Book of Jubilees. Kugel's stated aim is \'to understand what the text is saying and why it is saying it,\' and in particular to explore the numerous bits of biblical interpretation found in Jubilees and their connection to other exegetical writings of the Second Temple period. Subsequent chapters focus on the possibility that Jubilees had more than one author, as well as on the book's specific relationship to four other Second Temple texts: the Genesis Apocryphon, the Aramaic Levi Document, 4Q225 Pseudo-Jubilees, and the writings of Philo of Alexandria.